Lysosome: much more than a degradative organelle - Medina, Diego (Henry Stewart Talks, 2018)
Lysosome as degradative organelle, Transcriptional regulation of lysosomal and autophagic function, Promoting clearance through overexpression of TFEB in lysosomal storage disorders, TFEB regulation by phosphorylation, Imaging approaches to identify phosphatase regulating TFEB nuclear translocation, Role of the lysosomal calcium channel TRPML1 in TFEB nuclear translocation